Perceived Need for Mental Health Treatment and the Mental Health Response to the COVID-19 Pandemic in the United States. Issue 1 (2nd January 2022) - Breslau, Joshua; North, Carol S.; Finucane, Melissa L.; Roth, Elizabeth; Collins, Rebecca L.
Abstract : Objective : Population-based information on the extent of perceived need for mental health treatment and clinically significant psychological distress can help inform strategies for responding to the mental health impact of the COVID-19 pandemic. Methods : A representative sample of U.S. adults, age 20 and over (N = 1, 957), completed surveys in May and June 2020. Potential target populations were distinguished based on perceived need for mental health treatment and psychological distress, assessed by the Kessler-6, among those without perceived need. Populations were characterized with respect to demographic characteristics and prior mental health treatment history using logistic regression models. Results : The prevalence of perceived need for mental health treatment was 21%. Perceived need was strongly associated with pre-pandemic treatment history; compared to those with no treatment history, perceived need was dramatically higher among those in treatment when the pandemic began (OR = 53.8 95% CI 28.2–102.8) and those with pre-pandemic treatment history (OR = 9.3, 95% CI 5.1–16.8). Among the 79% who did not perceive need, moderate or greater distress was reported by 19% and was associated with younger age and Hispanic ethnicity (OR = 2.1, 95% CI 1.2–3.6). Conclusions : In the U.S., where mental health treatment is relatively common, mental health treatment response during the pandemic, and perhaps other crises, should target people with a history of mental health treatment. Outreach to people less likely to seek care on their own despite clinically significant distress should target Hispanic populations.